Herpes simplex virus 2 hepatitis in a lung transplant recipient: a diagnostic challenge. Issue 6 (5th November 2015) - Hirschi, S.; Biondini, D.; Ohana, M.; Solis, M.; D'Urso, A.; Rosner, V.; Kessler, R.
Abstract: Herpes simplex virus (HSV) hepatitis is a rare and serious complication in immunocompromised patients. We report the case of an HSV hepatitis occurring 4 years after lung transplantation in a cystic fibrosis patient. The presentation was nonspecific, mimicking acute cholecystitis; orogenital signs were absent. The diagnosis was made based on viral cultures performed during cholecystectomy and confirmed by blood quantitative polymerase chain reaction. Although the diagnosis and treatment were delayed, the patient fully recovered with acyclovir, reduced immunosuppression, and intravenous immunoglobulins. The diagnostic difficulties, prognostic factors, and treatments of this infection are discussed.